Can changes to improve person-centred maternity care be spread across public health facilities in Uttar Pradesh, India?. Issue 1 (1st January 2021) - Sudhinaraset, May; Giessler, Katie; Nakphong, Michelle Kao; Roy, Kali Prosad; Sahu, Ananta Basudev; Sharma, Kovid; Montagu, Dominic; Green, Cathy
Abstract: Poor quality person-centred maternity care (PCMC) leads to delays in care and adverse maternal and newborn outcomes. This study describes the impact of spreading a Change Package, or interventions that other health facilities had previously piloted and identified as successful, to improve PCMC in public health facilities in Uttar Pradesh, India. A quasi-experimental design was used including matched control-intervention facilities and pre–post data collection. This study took place in Uttar Pradesh, India in 2018–2019. Six large public health facilities participated in the evaluation of the spread study, including three intervention and three control facilities. Intervention facilities were introduced to a quality improvement (QI) Change Package to improve PCMC. In total, 1200 women participated in the study, including 600 women at baseline and 600 women at endline. Difference-in-difference estimators are used to examine the impact of spreading a QI Change Package across spread sites vs. control sites and at baseline and endline using a validated PCMC scale. Out of a 100-point scale, a 24.93 point improvement was observed in overall PCMC scores among spread facilities compared to control facilities from baseline to endline (95% CI: 22.29, 27.56). For the eight PCMC indicators that the Change Package targeted, spread facilities increased 33.86 points (95% CI: 30.91, 36.81) relative to control facilities across survey rounds. Findings suggest that spread of a PCMC Change Package results in improved experiences of care for women as well as secondary outcomes, including clinical quality, nurse and doctor visits, and decreases in delivery problems. Trial registration: ClinicalTrials.gov identifier: NCT04208841. .